Double-phase high-chromium cast iron alloy and preparation method and application thereof
By designing the chemical composition and heat treatment process of the duplex high-chromium cast iron alloy, an austenitic + ferrite matrix and M23C6 carbides are formed, which solves the problem of insufficient mechanical properties of high-chromium cast iron alloy at high temperature, achieves a balance between high wear resistance and corrosion resistance, and extends the service life of the alloy.
Patent Information
- Application Number
- CN202480002507.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing high-chromium cast iron alloys have insufficient mechanical properties at high temperatures, making it impossible to achieve both high wear resistance and high corrosion resistance. Furthermore, they are prone to cracking under thermal expansion and thermal cycling, which affects the fatigue life of the alloy.
The alloy is a duplex high-chromium cast iron alloy with a chemical composition including C 1.0%-2.5%, Si 0.5%-2.0%, Mn 0.5%-2.0%, Cr 30.0%-45.0%, Ni 5.0%-9.0%, Mo 1.0%-4.0%, Cu 1.0%-4.0%, V 0.1%-0.4%, Ti 0.1%-0.4%, rare earth elements 0.2%-0.5%, and N 0.1%-0.3%. The microstructure is austenite + ferrite, and the matrix contains carbides. Through a specific heat treatment process, M23C6 carbides are formed, which improves the hardness and thermal fatigue resistance of the alloy.
It maintains high wear resistance and corrosion resistance at high temperatures, reduces crack initiation and propagation, extends the service life of the alloy, and is suitable for high-temperature environments.
Smart Images

Figure CN119585456A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of alloy materials, and in particular to a duplex high-chromium cast iron alloy and a preparation method and application thereof. Background Art
[0002] Conventional high-chromium cast iron alloys have a high carbide content and high wear resistance, making them particularly suitable for use in high-speed fluid abrasive media. However, when there is a certain amount of acid in the medium, its corrosion resistance is limited. In contrast, solution-treated austenitic-ferritic duplex stainless steel has high corrosion resistance, but its wear resistance is often not good enough. To improve the wear resistance of duplex stainless steel, annealing can be carried out at 600-950°C, in which ferrite containing chromium, molybdenum and silicon can form a harder intermetallic phase. However, this intermetallic phase is harmful to duplex stainless steel, causing localized corrosion, reducing corrosion resistance, and making the alloy brittle and easy to break, affecting mechanical properties.
[0003] The operating temperature of conventional high-chromium cast iron alloy slurry pumps is below 100°C. However, under high temperature (above 160°C) conditions, due to thermal expansion and thermal cycling effects, the stress generated inside the alloy easily leads to the initiation and expansion of cracks, thereby reducing the fatigue life of the alloy. In addition, high temperature may also cause thermal fatigue of the alloy, that is, fatigue damage caused by temperature cycling.
[0004] Therefore, there is an urgent need to provide an alloy material with high wear resistance, high corrosion resistance and good high-temperature mechanical properties to increase the service life of the flow-through components of the slurry pump. Summary of the invention
[0005] The purpose of this application is to overcome the above-mentioned technical deficiencies, propose a dual-phase high-chromium cast iron alloy and its preparation method and application, and solve the technical problems in the prior art that alloy materials cannot take into account both high wear resistance and high corrosion resistance and have insufficient mechanical properties at high temperatures.
[0006] In a first aspect, the present application provides a duplex high chromium cast iron alloy, whose chemical composition, measured by mass percentage, includes: C 1.0%-2.5%, Si 0.5%-2.0%, Mn 0.5%-2.0%, Cr 30.0%-45.0%, Ni 5.0%-9.0%, Mo 1.0%-4.0%, Cu 1.0%-4.0%, V 0.1%-0.4%, Ti 0.1%-0.4%, rare earth 0.2%-0.5%, N 0.1%-0.3%, and the rest is Fe and unavoidable impurities; the microstructure of the duplex high chromium cast iron alloy is austenite + ferrite, and contains carbides.
[0007] In a second aspect, the present application provides a method for preparing a duplex high chromium cast iron alloy, comprising the following steps: S1. Weigh raw materials according to the chemical composition and proportion of the duplex high chromium cast iron alloy; S2, preparing raw materials into molten steel; S3, casting the molten steel, and forming an alloy casting after cooling and solidification; S4. Heat-treating the alloy casting to obtain a duplex high-chromium cast iron alloy.
[0008] In a third aspect, the present application provides the use of the above-mentioned duplex high chromium cast iron alloy in the preparation of flow-through components of a slurry pump.
[0009] Compared with the prior art, the beneficial effects of this application include: By using carbides to harden the austenite-ferrite dual-phase matrix structure, the present application can improve the hardness, wear resistance, high-temperature mechanical properties and thermal fatigue resistance of the alloy while maintaining corrosion resistance, and ultimately can be applied to various industrial fields requiring high strength, wear resistance, corrosion resistance and high temperature resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 This is a microstructure diagram of the duplex high chromium cast iron alloy in Example 2 of the present application. DETAILED DESCRIPTION
[0011] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0012] In a first aspect, the present application provides a duplex high chromium cast iron alloy, whose chemical composition, measured by mass percentage, includes: C 1.0%-2.5%, Si 0.5%-2.0%, Mn 0.5%-2.0%, Cr 30.0%-45.0%, Ni 5.0%-9.0%, Mo 1.0%-4.0%, Cu 1.0%-4.0%, V 0.1%-0.4%, Ti 0.1%-0.4%, rare earth 0.2%-0.5%, N 0.1%-0.3%, and the rest is Fe and unavoidable impurities; the microstructure of the duplex high chromium cast iron alloy is austenite (γ phase) + ferrite (α phase), and contains carbides.
[0013] Specifically, the mass percentage of C can be 1.0%, 1.2%, 1.5%, 1.7%, 2%, 2.2%, 2.5%, etc., or any other value within the range of 1.0%-2.5%.
[0014] Specifically, the mass percentage of Si can be 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.7%, 2.0%, etc., or any other value within the range of 0.5%-2.0.
[0015] Specifically, the mass percentage of Mn can be 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.7%, 2.0%, etc., or any other value within the range of 0.5%-2.0.
[0016] Specifically, the mass percentage of Cr can be 30%, 32%, 35%, 37%, 40%, 42%, 45%, etc., or any other value within the range of 30.0%-45.0%.
[0017] Specifically, the mass percentage of Ni can be 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, etc., or any other value within the range of 5.0%-9.0%.
[0018] Specifically, the mass percentage of Mo can be 1.0%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, etc., or any other value within the range of 1.0%-4.0%.
[0019] Specifically, the mass percentage of Cu can be 1.0%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, etc., or any other value within the range of 1.0%-4.0%.
[0020] Specifically, the mass percentage of V can be 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, etc., or any other value within the range of 0.1%-0.4%.
[0021] Specifically, the mass percentage of Ti can be 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, etc., or any other value within the range of 0.1%-0.4%.
[0022] Specifically, the mass percentage of rare earth can be 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, etc., or any other value within the range of 0.2%-0.5%.
[0023] Specifically, the mass percentage of N can be 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, etc., or any other value within the range of 0.1%-0.3%.
[0024] It should be pointed out that in specific settings, the above-mentioned dosage ranges of the chemical components can be used for combination.
[0025] Alloy elements can change the metal's organizational structure, improve the material's hardness, and increase corrosion resistance. The functions of the alloy elements in the duplex high chromium cast iron of this application are as follows: Carbon: Carbon is the main element that constitutes carbides in high chromium cast iron alloys. The mass fraction of carbon largely determines the volume fraction of carbides. However, excessive carbon will lead to the formation of coarse carbides, thereby reducing toughness, and in severe cases, graphitization will occur, thereby reducing the mechanical properties of the material. Taking all factors into consideration, this application controls the C content range to 1.0%-2.5%.
[0026] Silicon: Silicon is a good deoxidizer. During the solidification process of high chromium cast iron, it can promote the formation of ferrite and carbide, help form fine and uniform carbide particles, and improve its comprehensive mechanical properties. Taking all factors into consideration, the content of Si in this application is controlled within the range of 0.5%-2.0%.
[0027] Manganese: Manganese is a strong austenite-forming element that can be quickly dissolved in the alloy matrix to improve the hardenability of high-chromium cast iron. At the same time, a small amount of manganese is dissolved in carbides to appropriately increase their hardness. Taking all factors into consideration, the present application controls the content of Mn to 0.5%-2.0%.
[0028] Chromium: Chromium can significantly improve the wear resistance of the material by forming carbides with carbon, and can also form a dense chromium oxide passivation film on the surface of the material, thereby improving the corrosion resistance of the material. Taking all factors into consideration, the content of Cr in this application is controlled within the range of 30.0%-45.0%.
[0029] Nickel: Nickel can expand the austenite phase region and is the main alloy element for stabilizing austenite, which is beneficial to improving the acid resistance and medium corrosion resistance of the material. Taking comprehensive considerations, the present application controls the content range of Ni to 5.0%-9.0%.
[0030] Molybdenum: Mo can reduce the critical cooling rate of high chromium cast iron, so that high chromium cast iron can also obtain a uniform hardening effect in a larger cross-sectional thickness, thereby improving the hardenability of high chromium cast iron. Taking comprehensive considerations, the content range of Mo in this application is controlled to be 1.0%-4.0%.
[0031] Copper: Copper can improve corrosion resistance, mechanical properties and high temperature performance in high chromium cast iron, refine grains and increase hardenability, significantly enhancing the comprehensive performance of the alloy. Taking all factors into consideration, the content of Cu in this application is controlled within the range of 1.0%-4.0%.
[0032] Vanadium: Vanadium can refine primary austenite dendrites, thereby refining the structure and grain of the material and improving the mechanical properties. Taking all factors into consideration, the present application controls the V content range to 0.1%-0.4%.
[0033] Titanium: Titanium is a strong carbide-forming element, which can refine the carbides of high-chromium cast iron and improve wear resistance. Taking all factors into consideration, the content of Ti in this application is controlled within a range of 0.1%-0.4%.
[0034] Rare earth: Rare earth not only has strong deoxidation and desulfurization capabilities, which can reduce the adverse effects of harmful elements such as oxygen and sulfur on the performance of high chromium cast iron, but also can refine the grains of high chromium cast iron, change the morphology and distribution of carbides, make them smaller, more uniform and isolated, and improve the toughness of the matrix. Taking all factors into consideration, this application controls the rare earth content range to 0.2%-0.5%.
[0035] Nitrogen: forms austenite and improves corrosion resistance. However, as a non-metallic element, nitrogen has limited solubility in metals. If nitrogen is added in too high an amount, nitrogen pores will precipitate during the solidification of the metal, causing pores in the casting. Taking all factors into consideration, this application controls the N content range to 0.1%-0.3%.
[0036] The duplex high chromium cast iron alloy of the present application can ensure the formation of austenite + ferrite matrix structure after heat treatment and generate certain carbides in the matrix by controlling the alloy composition and ratio within the above range. A part of the chromium in the alloy composition forms carbides with carbon, while there is still enough chromium in the matrix to form a corrosion-resistant chromium oxide film. In addition, there is enough nickel and copper to ensure its high electrode potential, so the corrosion resistance of the alloy will not be reduced due to the consumption of part of the chromium in the carbide formation process. The duplex high chromium cast iron alloy of the present application has excellent corrosion resistance and mechanical properties at high temperatures, and can meet the requirements of corrosion resistance and wear resistance at high temperatures (160℃-170℃). At high temperatures and alternating temperatures, the refined alloy structure can reduce internal stress concentration, reduce crack initiation and expansion, and improve the alloy's heat fatigue resistance.
[0037] In this embodiment, the unavoidable impurities include S and P.
[0038] Specifically, the mass percentage of S can be 0.01%, 0.015%, 0.02%, 0.025%, 0.03%, 0.035%, 0.04%, 0.045%, 0.05%, etc., or any other value within the range of 0.01%-0.05%.
[0039] Specifically, the mass percentage of P can be 0.01%, 0.015%, 0.02%, 0.025%, 0.03%, 0.035%, 0.04%, 0.045%, 0.05%, etc., or any other value within the range of 0.01%-0.05%.
[0040] In this embodiment, the type of carbide is M 23 C 6 Carbide, and M 23 C 6 The volume proportion of carbides is 20%-40%. If the proportion of carbides is too low, the hardness of the alloy will not be improved enough; if the proportion of carbides is too high, the matrix structure will not be formed enough, and the most basic mechanical strength of the metal cannot be guaranteed.
[0041] In this embodiment, the rare earth includes at least one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, and europium.
[0042] In the present embodiment, the Rockwell hardness of the dual-phase high chromium cast iron alloy is greater than HRC40, and further greater than HRC42.
[0043] In this embodiment, the duplex high chromium cast iron alloy is corroded in sulfuric acid at 165° C. and pH=2 for 168 hours, and the corrosion rate is less than 0.1 mm / a, and further less than 0.08 mm / a.
[0044] In a second aspect, the present application provides a method for preparing a duplex high chromium cast iron alloy, comprising the following steps: S1. Weigh raw materials according to the chemical composition and proportion of the duplex high chromium cast iron alloy; S2, preparing raw materials into molten steel; S3, casting the molten steel, and forming an alloy casting after cooling and solidification; S4. Heat-treating the alloy casting to obtain a duplex high-chromium cast iron alloy.
[0045] The present application produces an austenite + ferrite matrix and certain carbides in the matrix through the combination of alloy composition and heat treatment process, so that the obtained duplex high chromium cast iron alloy not only has high wear resistance and high corrosion resistance, but also has good high-temperature mechanical properties. When it is used for the flow-through components of a slurry pump, the service life of the flow-through components of the slurry pump can be improved.
[0046] In this embodiment, the raw materials include: an iron source, a carbon source, a silicon source, a manganese source, a chromium source, a nickel source, a molybdenum source, a copper source, a vanadium source, a titanium source, a rare earth source and a nitrogen source. The present application does not limit the types of iron source, carbon source, silicon source, manganese source, chromium source, nickel source, molybdenum source, copper source, vanadium source, titanium source, rare earth source and nitrogen source, and those skilled in the art can select according to actual conditions. For example, the iron source can be pure iron or an iron alloy, the carbon source can be scrap steel, the silicon source can be ferrosilicon, silicon calcium, the manganese source can be ferromanganese, electrolytic manganese, the chromium source can be ferrochrome, micro-carbon chromium, chromium nitride, the nickel source can be a nickel plate, the molybdenum source can be ferromolybdenum, the copper source can be a copper plate, the nitrogen source can be chromium nitride, the vanadium source can be ferrovanadium, the titanium source can be ferrotitanium, the rare earth source can be a rare earth ferrosilicon alloy, the like.
[0047] In this implementation, step S2 specifically includes: S21, mixing and smelting an iron source, a carbon source, a silicon source, a manganese source, a chromium source, a nickel source, a molybdenum source, a copper source, and a nitrogen source until the mixture is clear, thereby obtaining a first molten steel; S22, deoxidizing the first molten steel to obtain a second molten steel; S23, adding a vanadium source and a titanium source to the second molten steel to obtain a third molten steel; S24, mixing the third molten steel and the rare earth source to obtain target molten steel.
[0048] The present invention adds vanadium source and titanium source after deoxidation treatment, so that the two sources work together during cooling and are enriched at the carbide grain boundaries, hindering the preferential growth of carbides and further refining the primary carbides.
[0049] Preferably, in step S21, the smelting temperature is 1550°C-1600°C, including but not limited to 1550°C, 1560°C, 1570°C, 1580°C, 1590°C, 1600°C, etc.
[0050] Preferably, step S21 further includes: detecting whether the content of each component in the pre-furnace analysis sample meets the chemical composition requirements of the target alloy; if yes, continuing to perform the subsequent deoxidation treatment steps; otherwise, adjusting the composition of the pre-furnace analysis sample according to the chemical composition of the target alloy until the chemical composition requirements of the target alloy are met.
[0051] Preferably, in step S22, the deoxidation process includes: adding a deoxidizer to the first molten steel for deoxidation treatment.
[0052] In some specific embodiments of the present application, the deoxidizer is a silicon-calcium alloy, and the amount of the deoxidizer added is 0.1%-0.3% of the mass of the first molten steel, including but not limited to 0.1%, 0.2%, 0.3%, etc.
[0053] Preferably, in step S22, the temperature of the deoxidation treatment is 1550°C-1600°C, including but not limited to 1550°C, 1560°C, 1570°C, 1580°C, 1590°C, 1600°C, etc.; the time of the deoxidation treatment is 3-10min, including but not limited to 3min, 5min, 7min, 10min, etc.
[0054] Preferably, in step S24, the process of mixing the third molten steel and the rare earth source comprises: adding the rare earth source into the ladle in advance, and then pouring the third molten steel with the temperature adjusted to 1500° C.-1550° C. into the ladle.
[0055] In this embodiment, in step S3, the casting temperature is 1400°C-1450°C, including but not limited to 1400°C, 1410°C, 1420°C, 1430°C, 1440°C, 1450°C, etc.
[0056] In this embodiment, in step S4, during the heat treatment, the heating rate is ≤50°C / h, including but not limited to 10°C / h, 20°C / h, 30°C / h, 40°C / h, 50°C / h, etc.; the heat treatment temperature is 1000°C-1100°C, including but not limited to 1000°C, 1020°C, 1040°C, 1060°C, 1080°C, 1100°C, etc.; the heat treatment time is 2-5 hours, including but not limited to 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, etc.; after the heat treatment is completed, the furnace is taken out and air-cooled to room temperature.
[0057] The heat treatment process of the present application is simple and time-saving. By controlling the temperature of the heat treatment within the above range, the present application can ensure that the ferrite and austenite contents in the matrix are equivalent, so that the alloy has the best performance. If the temperature of the heat treatment is too low, the brittle phase will not be completely dissolved into the matrix, thereby affecting the mechanical properties of the alloy. At the same time, the brittle phase will reduce the corrosion resistance due to the chromium-rich surrounding chromium-poor; if the temperature of the heat treatment is too high, energy will be wasted and the casting will be severely oxidized.
[0058] In a third aspect, the present application provides the use of the above-mentioned duplex high chromium cast iron alloy in the preparation of flow-through components of a slurry pump.
[0059] The above-mentioned slurry pump of the present application can be applied to the fields of mining, metallurgy, etc.
[0060] Example 1 The chemical composition of the duplex high chromium cast iron alloy provided in this embodiment is shown in Table 1.
[0061] Table 1 Alloy chemical composition (wt.%)
[0062] The preparation steps include: (1) According to Table 1 and the alloy composition content of scrap steel, ferrosilicon, ferromanganese, ferrochrome, nickel plate, ferromolybdenum, copper plate and chromium nitride, calculate the weight required for each type of charge based on a 400kg medium frequency furnace.
[0063] (2) After weighing the required weight according to each charge, scrap steel, nickel plate, copper plate, ferrochrome, ferromolybdenum, ferromanganese, ferrosilicon and chromium nitride are added into the medium frequency furnace in the order of scrap steel, and the temperature is raised to 1550°C. After the charge is melted, the first molten steel is obtained; silicon-calcium alloy accounting for 0.2% of the mass of the first molten steel is added to the first molten steel for deoxidation treatment for 5 minutes. After the deoxidation is completed, the second molten steel is obtained.
[0064] (3) Add ferrovanadium and ferrotitanium to the second molten steel to obtain a third molten steel; when the temperature of the third molten steel is adjusted to 1510°C, add rare earth ferrosilicon alloy (grade 195023) into the ladle, and pour the third molten steel into the ladle to obtain the target molten steel; when the temperature of the target molten steel drops to 1400°C, pour the target molten steel into the mold cavity, and obtain the required slurry pump casting after cooling and solidification.
[0065] (4) The slurry pump casting is heat treated to obtain a duplex high chromium cast iron alloy. The specific parameters of the heat treatment are as follows: heating to 1000°C at a rate of 50°C per hour, keeping the temperature for 2 hours, and then cooling to room temperature in air.
[0066] Take the furnace sample (the sample that is put into the furnace for heat treatment together with the casting, its alloy composition and heat treatment process are consistent with the casting, and its performance represents the performance of the casting), prepare the Φ30×3mm corrosion sample, corrode in dilute sulfuric acid at 165℃ and pH=2 for 168 hours, and measure its uniform corrosion rate (mm / a, millimeter / year); prepare the Φ70×40mm round sample to test the Rockwell hardness (HRC); prepare the 50×30×3mm sheet sample, and conduct a temperature change test in the temperature range of 25℃-175℃ to detect whether there are cracks on the sample surface under temperature changes. Its performance indicators are shown in Table 2.
[0067] Table 2 Hardness, uniform corrosion rate and crack tendency of the alloy in Example 1
[0068] (The test results of Rockwell hardness and uniform corrosion rate are the average of three tests. No cracks in the crack tendency result means that there are no cracks in three measurements. Cracks in the crack tendency result means that at least one crack occurs in three measurements.) Example 2 The chemical composition of the duplex high chromium cast iron alloy provided in this embodiment is shown in Table 3.
[0069] Table 3 Alloy chemical composition (wt.%)
[0070] The preparation steps include: (1) According to Table 3 and the alloy composition contents of scrap steel, ferrosilicon, ferromanganese, ferrochrome, nickel plate, ferromolybdenum, copper plate and chromium nitride, calculate the required weight of various types of furnace materials based on a 400kg medium frequency furnace.
[0071] (2) After weighing the required weight according to each charge, scrap steel, nickel plate, copper plate, ferrochrome, ferromolybdenum, ferromanganese, ferrosilicon and chromium nitride are added into the medium frequency furnace in the order of scrap steel, and the temperature is raised to 1568°C. After the charge is melted, the first molten steel is obtained; silicon-calcium alloy accounting for 0.2% of the mass of the first molten steel is added to the first molten steel for deoxidation treatment for 5 minutes. After the deoxidation is completed, the second molten steel is obtained.
[0072] (3) Add ferrovanadium and ferrotitanium to the second molten steel to obtain a third molten steel; when the temperature of the third molten steel is adjusted to 1517°C, add rare earth ferrosilicon alloy (grade 195023) into the ladle, and pour the third molten steel into the ladle to obtain the target molten steel; when the temperature of the target molten steel drops to 1418°C, pour the target molten steel into the mold cavity, and after cooling and solidification, obtain the required slurry pump casting.
[0073] (4) The slurry pump casting is heat treated to obtain a duplex high chromium cast iron alloy. The specific parameters of the heat treatment are as follows: heating to 1035°C at a rate of 40°C per hour, keeping the temperature for 3 hours, and then cooling to room temperature in air.
[0074] Take the furnace sample to prepare a Φ30×3mm corrosion sample, corrode it in dilute sulfuric acid at 165℃ and pH=2 for 168 hours, and measure its uniform corrosion rate (mm / a, millimeter / year); prepare a Φ70×40mm round sample to test Rockwell hardness (HRC); prepare a 50×30×3mm sheet sample, and conduct a temperature change test within the temperature range of 25℃-175℃ to detect whether cracks are generated on the sample surface under temperature changes. Its performance indicators are shown in Table 4.
[0075] Table 4 Hardness, uniform corrosion rate and crack tendency of the alloy in Example 2
[0076] (The test results of Rockwell hardness and uniform corrosion rate are the average of three tests. No cracks in the crack tendency result means that there are no cracks in three measurements. Cracks in the crack tendency result means that at least one crack occurs in three measurements.) Figure 1 is a microstructure diagram of the duplex high chromium cast iron alloy in Example 2 of the present application. Figure 1 ,pass Figure 1It can be seen that the structure has a dual-phase matrix structure of austenite (γ phase) + ferrite (α phase), and M is evenly distributed around the dual-phase matrix structure. 23 C 6 Type carbide.
[0077] Example 3 The chemical composition of the duplex high chromium cast iron alloy provided in this embodiment is shown in Table 5.
[0078] Table 5 Alloy chemical composition (wt.%)
[0079] The preparation steps include: (1) According to Table 5, calculate the weight of each type of charge required for a 400kg medium frequency furnace based on the alloy component contents of scrap steel, ferrosilicon, ferromanganese, ferrochrome, nickel plate, ferromolybdenum, copper plate, and chromium nitride.
[0080] (2) After weighing the required weight according to each charge, scrap steel, nickel plate, copper plate, ferrochrome, ferromolybdenum, ferromanganese, ferrosilicon and chromium nitride are added into the medium frequency furnace in the order of scrap steel, and the temperature is raised to 1585°C. After the charge is melted, the first molten steel is obtained; silicon-calcium alloy accounting for 0.2% of the mass of the first molten steel is added to the first molten steel for deoxidation treatment for 5 minutes. After the deoxidation is completed, the second molten steel is obtained.
[0081] (3) Add ferrovanadium and ferrotitanium to the second molten steel to obtain a third molten steel; when the temperature of the third molten steel is adjusted to 1535°C, add rare earth ferrosilicon alloy (grade 195023) into the ladle, and pour the third molten steel into the ladle to obtain the target molten steel; when the temperature of the target molten steel drops to 1436°C, pour the target molten steel into the mold cavity, and obtain the desired slurry pump casting after cooling and solidification.
[0082] (4) The slurry pump casting is heat treated to obtain a duplex high chromium cast iron alloy. The specific parameters of the heat treatment are as follows: heating to 1070°C at a rate of 30°C per hour, keeping the temperature for 4 hours, and then cooling to room temperature in air.
[0083] Take the furnace sample to prepare a Φ30×3mm corrosion sample, corrode it in dilute sulfuric acid at 165℃ and pH=2 for 168 hours, and measure its uniform corrosion rate (mm / a, millimeter / year); prepare a Φ70×40mm round sample to test Rockwell hardness (HRC); prepare a 50×30×3mm sheet sample, and conduct a temperature change test within the temperature range of 25℃-175℃ to detect whether cracks are generated on the sample surface under temperature changes. Its performance indicators are shown in Table 6.
[0084] Table 6 Hardness, uniform corrosion rate and crack tendency of the alloy in Example 3
[0085] (The test results of Rockwell hardness and uniform corrosion rate are the average of three tests. No cracks in the crack tendency result means that there are no cracks in three measurements. Cracks in the crack tendency result means that at least one crack occurs in three measurements.) Example 4 The chemical composition of the duplex high chromium cast iron alloy provided in this embodiment is shown in Table 7.
[0086] Table 7 Alloy chemical composition (wt.%)
[0087] The preparation steps include: (1) According to Table 7 and the alloy composition content of scrap steel, ferrosilicon, ferromanganese, ferrochrome, nickel plate, ferromolybdenum, copper plate and chromium nitride, calculate the required weight of various types of furnace materials based on a 400kg medium frequency furnace.
[0088] (2) After weighing the required weight according to each charge, scrap steel, nickel plate, copper plate, ferrochrome, ferromolybdenum, ferromanganese, ferrosilicon and chromium nitride are added into the medium frequency furnace in the order of scrap steel, and the temperature is raised to 1600°C. After the charge is melted, the first molten steel is obtained; silicon-calcium alloy accounting for 0.2% of the mass of the first molten steel is added to the first molten steel for deoxidation treatment for 5 minutes. After the deoxidation is completed, the second molten steel is obtained.
[0089] (3) Add ferrovanadium and ferrotitanium to the second molten steel to obtain a third molten steel; when the temperature of the third molten steel is adjusted to 1550°C, add rare earth ferrosilicon alloy (grade 195023) into the ladle, and pour the third molten steel into the ladle to obtain the target molten steel; when the temperature of the target molten steel drops to 1450°C, pour the target molten steel into the mold cavity, and obtain the desired slurry pump casting after cooling and solidification.
[0090] (4) The slurry pump casting is heat treated to obtain a duplex high chromium cast iron alloy. The specific parameters of the heat treatment are as follows: heating to 1100°C at a rate of 20°C per hour, keeping the temperature for 5 hours, and then cooling to room temperature in air.
[0091] Take the furnace sample to prepare a Φ30×3mm corrosion sample, corrode it in dilute sulfuric acid at 165℃ and pH=2 for 168 hours, and measure its uniform corrosion rate (mm / a, millimeter / year); prepare a Φ70×40mm round sample to test Rockwell hardness (HRC); prepare a 50×30×3mm sheet sample, and conduct a temperature change test within the temperature range of 25℃-175℃ to detect whether cracks are generated on the sample surface under temperature changes. Its performance indicators are shown in Table 8.
[0092] Table 8 Hardness, uniform corrosion rate and crack tendency of the alloy in Example 4
[0093] (The test results of Rockwell hardness and uniform corrosion rate are the average of three tests. No cracks in the crack tendency result means that there are no cracks in three measurements. Cracks in the crack tendency result means that at least one crack occurs in three measurements.) Comparative Example 1 The cast iron alloy provided in this comparative example is adjusted according to Example 2, except that the carbon content is relatively low, at 0.7%. Its chemical composition is shown in Table 9.
[0094] Table 9 Alloy chemical composition (wt.%)
[0095] The preparation steps are consistent with those in Example 2.
[0096] Take the furnace sample to prepare a Φ30×3mm corrosion sample, corrode it in dilute sulfuric acid at 165℃ and pH=2 for 168 hours, and measure its uniform corrosion rate (mm / a, millimeter / year); prepare a Φ70×40mm round sample to test Rockwell hardness (HRC); prepare a 50×30×3mm sheet sample, and conduct a temperature change test within the temperature range of 25℃-175℃ to detect whether cracks are generated on the sample surface under temperature changes. Its performance indicators are shown in Table 10.
[0097] Table 10 Hardness, uniform corrosion rate and crack tendency of the alloy in Comparative Example 1
[0098] (The test results of Rockwell hardness and uniform corrosion rate are the average of three tests. No cracks in the crack tendency result means that there are no cracks in three measurements. Cracks in the crack tendency result means that at least one crack occurs in three measurements.) The uniform corrosion rate of the alloy produced in this comparative example meets the requirements, but the hardness is low. The main reason is that the carbon content of the alloy is lower than that of Example 2, the matrix structure is ferrite, and the carbide content is low at only about 15%, which cannot meet the requirements of medium wear resistance.
[0099] Comparative Example 2 The cast iron alloy provided in this comparative example is adjusted according to Example 3, except that the chromium content is lower, 25.2%. The chemical composition of the alloy is shown in Table 11.
[0100] Table 11 Alloy chemical composition (wt.%)
[0101] The preparation steps are consistent with those in Example 3.
[0102] Take the furnace sample to prepare a Φ30×3mm corrosion sample, corrode it in dilute sulfuric acid at 165℃ and pH=2 for 168 hours, and measure its uniform corrosion rate (mm / a, millimeter / year); prepare a Φ70×40mm round sample to test Rockwell hardness (HRC); prepare a 50×30×3mm sheet sample, and conduct a temperature change test within the temperature range of 25℃-175℃ to detect whether cracks are generated on the sample surface under temperature changes. Its performance indicators are shown in Table 12.
[0103] Table 12 Hardness, uniform corrosion rate and crack tendency of the alloy in Comparative Example 2
[0104] (The test results of Rockwell hardness and uniform corrosion rate are the average of three tests. No cracks in the crack tendency result means that there are no cracks in three measurements. Cracks in the crack tendency result means that at least one crack occurs in three measurements.) The alloy hardness of the comparative example meets the requirements, but the uniform corrosion rate at high temperature is high, with an average value of 0.272mm / a. The main reason is that the Cr content of the alloy is too little. After the Cr in the alloy and C form carbides, the Cr in the matrix is too low, resulting in its electrode potential being lower than that of the carbides, resulting in selective corrosion.
[0105] Comparative Example 3 The cast iron alloy provided in this comparative example is adjusted according to Example 4, except that the nickel content is lower, 4.5%. The chemical composition of the alloy is shown in Table 13.
[0106] Table 13 Alloy chemical composition (wt.%)
[0107] The preparation steps are consistent with those in Example 4.
[0108] Take the furnace sample to prepare a Φ30×3mm corrosion sample, corrode it in dilute sulfuric acid at 165℃ and pH=2 for 168 hours, and measure its uniform corrosion rate (mm / a, millimeter / year); prepare a Φ70×40mm round sample to test Rockwell hardness (HRC); prepare a 50×30×3mm sheet sample, and conduct a temperature change test within the temperature range of 25℃-175℃ to detect whether cracks are generated on the sample surface under temperature changes. Its performance indicators are shown in Table 14.
[0109] Table 14 Hardness, uniform corrosion rate and crack tendency of the alloy in Comparative Example 3
[0110] (The test results of Rockwell hardness and uniform corrosion rate are the average of three tests. No cracks in the crack tendency result means that there are no cracks in three measurements. Cracks in the crack tendency result means that at least one crack occurs in three measurements.) The hardness and uniform corrosion rate of the alloy produced in this comparative example meet the requirements, but after careful observation of the surface of the sample after the temperature change test, micro cracks were found in some parts of the sample. The main reason is that the low Ni content causes the alloy structure to be ferrite + carbide. In comparison, the high-temperature mechanical properties of ferrite are inferior to those of austenite.
[0111] Comparative Example 4 The cast iron alloy provided in this comparative example is adjusted according to Example 3, except that the heat treatment parameters are different. The specific parameters are as follows: heating to 950° C. at a rate of 30° C. per hour, keeping the temperature for 4 hours, and then cooling to room temperature in air.
[0112] Take the furnace sample to prepare a Φ30×3mm corrosion sample, corrode it in dilute sulfuric acid at 165℃ and pH=2 for 168 hours, and measure its uniform corrosion rate (mm / a, millimeter / year); prepare a Φ70×40mm round sample to test Rockwell hardness (HRC); prepare a 50×30×3mm sheet sample, and conduct a temperature change test within the temperature range of 25℃-175℃ to detect whether cracks are generated on the sample surface under temperature changes. Its performance indicators are shown in Table 15.
[0113] Table 15 Hardness, uniform corrosion rate and crack tendency of the alloy in Comparative Example 4
[0114] (The test results of Rockwell hardness and uniform corrosion rate are the average of three tests. No cracks in the crack tendency result means that there are no cracks in three measurements. Cracks in the crack tendency result means that at least one crack occurs in three measurements.) The alloy hardness of this comparative example is higher than that of Example 3, but the average uniform corrosion rate is 0.401 mm / a, which does not meet the corrosion resistance requirements. In addition, cracks appear on the surface of the sample after the temperature change test. The main reason is that the cast structure of the material is composed of austenite, σ brittle phase and M 23 C 6 Carbide composition, due to the low heat treatment temperature, the σ brittle phase is not completely dissolved and remains in the matrix structure. The σ phase is a phase with high hardness, but it will reduce the toughness of the material and increase the crack tendency. At the same time, the σ phase is rich in chromium, which leads to chromium depletion in the surrounding area and reduces its corrosion resistance.
[0115] Comparative Example 5 The hardness, uniform corrosion rate and crack tendency of BTSCr36Mo2Ni2Cu were tested using the same test method as in the embodiment. The performance indicators of BTSCr36Mo2Ni2Cu are shown in Table 16.
[0116] Table 16 Hardness, uniform corrosion rate and crack tendency of BTSCr36Mo2Ni2Cu
[0117] (The test results of Rockwell hardness and uniform corrosion rate are the average of three tests. No cracks in the crack tendency result means that there are no cracks in three measurements. Cracks in the crack tendency result means that at least one crack occurs in three measurements.) The alloy hardness in this comparative example is equivalent to that in the embodiment of the present application, but the corrosion and wear rate is significantly higher than that in the embodiment of the present application, and cracks are still generated on the surface of the sample when the temperature change test is carried out in the temperature range of 25°C-175°C, indicating that the duplex high chromium cast iron alloy of the present application has obvious advantages over the existing high chromium corrosion-resistant and high-wear cast iron.
[0118] Application Examples The slurry pump castings produced in Examples 1-4 did not show defects such as cracks, shrinkage holes, and pores after processing. After simulated working conditions and actual field trials, their corrosion rate was 40%-50% lower than that of the existing high-chromium, corrosion-resistant and high-wear cast iron BTSCr36Mo2Ni2Cu material. In a factory test, their service life was about 1.5 times that of the BTSCr36Mo2Ni2Cu material.
[0119] In summary, the dual-phase high-chromium cast iron alloy of the present application forms an austenite + ferrite + 20%-40% carbide structure by effectively designing the alloy composition of each element. After heat treatment, the hardness of the material is above HRC40, and the corrosion rate is less than 0.08mm / a in a corrosion test in sulfuric acid at 165℃ and pH=2, reaching the corrosion resistance standard (<0.1mm / a), and no cracks are generated on the surface of the sample in a temperature change test within the temperature range of 25℃-175℃.
[0120] The specific implementation methods of the present application described above do not constitute a limitation on the protection scope of the present application. Any other corresponding changes and modifications made according to the technical concept of the present application should be included in the protection scope of the claims of the present application.
Claims
1. A duplex high chromium cast iron alloy, characterized in that: The chemical composition includes, by mass percentage, C 1.0%-2.5%, Si 0.5%-2.0%, Mn 0.5%-2.0%, Cr 30.0%-45.0%, Ni 5.0%-9.0%, Mo 1.0%-4.0%, Cu1.0%-4.0%, V 0.1%-0.4%, Ti 0.1%-0.4%, rare earth 0.2%-0.5%, N 0.1%-0.3%, and the rest is Fe and unavoidable impurities; the microstructure of the duplex high chromium cast iron alloy is austenite + ferrite, and contains carbides.
2. The duplex high chromium cast iron alloy according to claim 1, characterized in that: The type of carbide is M 23 C6 carbide, and the M 23 The volume proportion of C6 carbide is 20%-40%.
3. The duplex high chromium cast iron alloy according to claim 1, characterized in that: The rare earth includes at least one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium and europium.
4. The duplex high chromium cast iron alloy according to claim 1, characterized in that: The Rockwell hardness of the duplex high chromium cast iron alloy is greater than HRC40; the duplex high chromium cast iron alloy is corroded in sulfuric acid at 165° C. and pH=2 for 168 hours, and its corrosion rate is less than 0.1 mm / a.
5. A method for preparing the duplex high chromium cast iron alloy according to any one of claims 1 to 4, characterized in that: The following steps are involved: Weigh the raw materials according to the chemical composition and proportion of the duplex high chromium cast iron alloy; preparing the raw materials into molten steel; Casting the molten steel and cooling and solidifying it to form an alloy casting; The alloy casting is heat treated to obtain a duplex high chromium cast iron alloy.
6. The method for preparing the dual-phase high chromium cast iron alloy according to claim 5, characterized in that: The step of preparing the raw materials into molten steel specifically comprises: Mixing and smelting an iron source, a carbon source, a silicon source, a manganese source, a chromium source, a nickel source, a molybdenum source, a copper source, and a nitrogen source until the mixture is clear, thereby obtaining a first molten steel; Deoxidizing the first molten steel to obtain a second molten steel; adding a vanadium source and a titanium source to the second molten steel to obtain a third molten steel; The third molten steel and a rare earth source are mixed to obtain target molten steel.
7. The method for preparing the dual-phase high chromium cast iron alloy according to claim 6, characterized in that: The smelting temperature is 1550°C-1600°C; The deoxidation process includes: adding a deoxidizer to the first molten steel for deoxidation; the deoxidizer is a silicon-calcium alloy, and the amount of the deoxidizer added is 0.1%-0.3% of the mass of the first molten steel; the temperature of the deoxidation treatment is 1550°C-1600°C, and the time of the deoxidation treatment is 3-10 minutes; The process of mixing the third molten steel and the rare earth source comprises: adding the rare earth source into the ladle in advance, and then pouring the third molten steel with the temperature adjusted to 1500° C.-1550° C. into the ladle.
8. The method for preparing the dual-phase high chromium cast iron alloy according to claim 5, characterized in that: The casting temperature is 1400°C-1450°C.
9. The method for preparing the dual-phase high chromium cast iron alloy according to claim 5, characterized in that: During the heat treatment, the heating rate is ≤50°C / h, the heat treatment temperature is 1000°C-1100°C, and the heat treatment time is 2-5 hours; after the heat treatment, the product is taken out of the furnace and air-cooled to room temperature.
10. Use of the duplex high chromium cast iron alloy according to any one of claims 1 to 4 in preparing flow-through components of a slurry pump.
Citation Information
Patent Citations
High-chromium cast iron and preparation method thereof
CN114395721A
Highly corrosion and wear resistant chilled casting
CN1148415A